2021
DOI: 10.1111/tpj.15229
|View full text |Cite
|
Sign up to set email alerts
|

Complexity untwined: The structure and function of cucumber (Cucumis sativus L.) shoot phloem

Abstract: Cucurbit phloem is complex, with large sieve tubes on both sides of the xylem (bicollateral phloem), and extrafascicular elements that form an intricate web linking the rest of the vasculature. Little is known of the physical interconnections between these networks or their functional specialization, largely because the extrafascicular phloem strands branch and turn at irregular angles. Here, export in the phloem from specific regions of the lamina of cucumber (Cucumis sativus L.) was mapped using carboxyfluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In our previous researches, the CsAAP3 (Sui et al ., 2018), which was mainly expressed in the internal phloem of fruit vascular bundles, and CsAAP6 (Sui et al ., 2021), which was most likely involved in amino acid transport in the external phloem of petiole, have been identified using transcriptome data. To examine tissue‐specific expression of cucumber CsAAPs , absolute qRT‐PCR was performed in various organs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous researches, the CsAAP3 (Sui et al ., 2018), which was mainly expressed in the internal phloem of fruit vascular bundles, and CsAAP6 (Sui et al ., 2021), which was most likely involved in amino acid transport in the external phloem of petiole, have been identified using transcriptome data. To examine tissue‐specific expression of cucumber CsAAPs , absolute qRT‐PCR was performed in various organs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although relatively extensive progress has been made in identification and functional characterization of amino acid transporters in Arabidopsis, rice, and other plants, few transporters were functionally characterized in cucumber. In previous works, we reported on the identification of CsAAP3 and CsAAP6 , which are associated with amino acid transport in vasculature of fruit and petiole respectively (Sui et al ., 2018, 2021). In this study, the CsAAP2 was found to be highly expressed in cucumber pericycle cells and closely related to root development.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the rapid growth of SWEETs research in Arabidopsis [ 2 , 13 , 14 , 28 , 29 ], rice [ 11 ], and maize [ 30 , 31 , 32 ], studies on SWEET homologues in other plant species such as tomato [ 33 ], watermelon [ 25 ], and the tea plant [ 15 , 16 ] have been reported, and findings have been updated. Although SWEETs are important versatile regulators and affect yield potential, only two cucumber CsSWEET genes have been reported in detail to date [ 21 , 22 , 23 ]. In this study, we characterized the CsSWEET2 gene in cucumber and found that overexpression of CsSWEET2 in Arabidopsis improves tolerance to cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its tropical origin and heat-loving habit, cucumber is extremely sensitive to cold stress. In previous studies, 17 CsSWEET genes were identified in the cucumber genome by bioinformatic analysis [ 19 , 20 ], among which are CsSWEET7a , responsible for sugar phloem unloading in cucumber fruits, receptacles, and nectaries [ 21 , 22 ], and CsSWEET12c , which is involved in promoting plant growth and flowering [ 23 ]. However, the exact roles of the other 15 CsSWEET genes in cucumber have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Among the only sugar transporters that can mediate the efflux of sugars across cell membranes, the 17 CsSWEETs identified in the cucumber genome [22] were the best candidates for genes that export sugars from anther tissues into anther locules. However, out of the seventeen CsSWEET genes, only three have been characterized in detail; CsSWEET2 enhances cold tolerance in plants [33]; CsSWEET7a is involved in hexose unloading in cucumber receptacles, nectaries, and fruits [26,27]; and CsSWEET12c promotes plant growth and blooming [39]. None of these three genes are related to pollen development.…”
Section: Introductionmentioning
confidence: 99%